Autologous collagen-induced chondrogenesis with high tibial osteotomy for large collapsed steroid-induced osteonecrosis in a patient with systemic lupus erythematosus: a case report and literature review - Dong Hwan Lee; Bo Seung Bae; Seon Ae Kim; Mi‑La Cho; Seok Jung Kim (BMC Musculoskeletal Disorders)
Abstract Background Secondary osteonecrosis (ON) of the knee poses a treatment challenge, especially in young patients with systemic lupus erythematosus (SLE) requiring ongoing steroid therapy. Joint-preserving options for large osteochondral defects are limited, and there are no standardized protocols. Case presentation We report the case of a 37-year-old female with a history of SLE and prior left total knee arthroplasty who presented with severe right knee pain and a progressive varus deformity. Imaging revealed a 4 × 2 cm osteochondral defect of the medial femoral condyle with over 10 mm depth and an 8° varus alignment. Given the patient’s young age and preference to avoid arthroplasty, we performed a combined medial opening high tibial osteotomy (HTO) and autologous collagen-induced chondrogenesis (ACIC) with iliac crest bone grafting. The procedure involved creation of large channels for graft placement and multiple drillings, followed by atelocollagen mixture gel application to enhance cartilage regeneration. The patient experienced progressive pain relief and functional improvement, achieving full weight bearing by 3 months. However, crutch-assisted ambulation was maintained until 6 months to reduce loading on the joint. Radiographs at 3, 9, and 18 months demonstrated gradual medial joint space widening. At 2-year follow-up, arthroscopic examination confirmed complete defect coverage with regenerated cartilage. No major complications occurred. Conclusion Medial opening HTO combined with ACIC and autologous bone grafting may offer a feasible single-stage, joint-preserving solution for large osteochondral defects in steroid-induced secondary ON, expanding treatment options for young SLE patients.